Arctic reindeer extend their visual range into the ultraviolet - Hogg, Christopher; Neveu, Magella; Stokkan, Karl-Arne; Folkow, Lars; Cottrill, Phillippa; Douglas, Ronald; Hunt, David M.; Jeffery, Glen (Journal of Experimental Biology, 2011)
The Arctic has extreme seasonal changes in light levels and is proportionally UV-rich because of scattering of the shorter wavelengths and their reflection from snow and ice. Here we show that the cornea and lens in Arctic reindeer do not block all UV and that the retina responds electrophysiologically to these wavelengths. Both rod and cone photoreceptors respond to UV at low-intensity stimulation. Retinal RNA extraction and in vitro opsin expression show that the response to UV is not mediated by a specific UV photoreceptor mechanism. Reindeer thus extend their visual range into the short wavelengths characteristic of the winter environment and periods of extended twilight present in spring and autumn. A specific advantage of this short-wavelength vision is the use of potential information caused by differential UV reflections known to occur in both Arctic vegetation and different types of snow. UV is normally highly damaging to the retina, resulting in photoreceptor degeneration. Because such damage appears not to occur in these animals, they may have evolved retinal mechanisms protecting against extreme UV exposure present in the daylight found in the snow-covered late winter environment.